2013
DOI: 10.1097/dcr.0b013e318282e790
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Tumor Stage Is an Independent Risk Factor of Postoperative Infectious Complications After Colorectal Surgery

Abstract: Advanced tumors increase the risk of infectious complications after colorectal resection, with other risk factors including malnutrition, obesity, and resection by laparotomy. Optimization of modifiable risk factors through nutritional repletion and the choice of a minimally invasive operation should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 37 publications
2
24
1
Order By: Relevance
“…The reduced invasiveness of the laparoscopic technique with less muscular trauma, less postoperative pain, less bowel manipulation, reduced inflammatory response and immunosuppression, and earlier postoperative activities may be considered to be the main reasons for explaining such results. 20 The conversion rate from laparoscopy to laparotomy was 14.2% higher than in most reported series [7% (range 0-25)] and probably reflects the multicentric character of our study including preliminary experiences. 13 Those converted patients were included in the laparoscopic group in an intent-to-treat analysis, reinforcing the beneficial effect of laparoscopy that we observed.…”
Section: Discussioncontrasting
confidence: 52%
“…The reduced invasiveness of the laparoscopic technique with less muscular trauma, less postoperative pain, less bowel manipulation, reduced inflammatory response and immunosuppression, and earlier postoperative activities may be considered to be the main reasons for explaining such results. 20 The conversion rate from laparoscopy to laparotomy was 14.2% higher than in most reported series [7% (range 0-25)] and probably reflects the multicentric character of our study including preliminary experiences. 13 Those converted patients were included in the laparoscopic group in an intent-to-treat analysis, reinforcing the beneficial effect of laparoscopy that we observed.…”
Section: Discussioncontrasting
confidence: 52%
“…Therefore, when age and sarcopenia were both included in the multivariate analysis, age was excluded as a confounding factor and sarcopenia became an independent risk factor. Several factors that were previously reported to be independent risk factors for complications after colorectal surgery, such as male gender [28] or advanced tumour stage [29], were not associated with postoperative complications in the present study. This may be due to the different patient characteristics and the different treatments.…”
Section: O262supporting
confidence: 44%
“…The frequency of superficial SSIs was similar in both groups. 16 Segal et al 17 found a similar association of disseminated cancer with organ space SSIs (adjusted odds ratio [AOR], 1.21; 95% CI, 1.02–1.44). 17 …”
Section: Discussionmentioning
confidence: 94%